Removal of Nitrogen, Phosphates, and Chemical Oxygen Demand from Community Wastewater by Using Treatment Wetlands Planted with Ornamental Plants in Different Mineral Filter Media - José Luis Marín-Muñiz; Gonzalo Ortega-Pineda; Irma Zitácuaro-Contreras; Monserrat Vidal-Álvarez; Karina E. Martínez-Aguilar; Luis M. Álvarez-Hernández; Sergio Zamora-Castro (Nitrogen)
This study aimed to explore the impact of various ornamental plants (Heliconia psittacorum, Etlingera elatior, Spatyphilum walisii) grown in different filter media (porous river rock (PR) and tepezyl (TZ)) on the removal of pollutants in vertical-subsurface-microcosm treatment wetlands (TWs). This study also sought to assess the adaptability of these plant species to TW conditions. Twenty-four microcosm systems were utilized, with twelve containing PR and twelve containing TZ as the filter media. Each porous media type had three units planted with each species, and three were left unplanted. Rural community wastewater was treated in the TWs. The results showed no significant differences in the effects of the porous media on pollutant removal performance (p > 0.05). However, it was noted that while both porous media were efficient, TZ, a residue of construction materials, is recommended for sites facing economic constraints. Additionally, the removal efficiency was found to be independent of the type of ornamental plant used (p > 0.05); however, the measured parameters varied with plant spp. The adaptation of the plants varied depending on the species. H. psittacorum grew faster and produced a larger number of flowers compared to the other species (20–22 cm). S. wallisii typically produced 7–8 flowers. E. elatior did not produce flowers, and some plants showed signs of slight disease and pests, with the leaves turning yellow. In terms of plant biomass, the type of porous media used did not have a significant effect on the production of above (p = 0.111) or below-ground biomass (p = 0.092). The removal percentages for COD in the presence and absence of plants were in the ranges of 64–77% and 27–27.7%, respectively. For TN, the numbers were 52–65% and 30–31.8%, and for N-NO3, they were 54–60% and 12–18%. N-NH4 saw removal rates of 67–71% and 28–33%, while P-PO4 saw removal rates of 60–72% and 22–25%. The difference in removal percentages between microcosms with and without plants ranged from 30 to 50%, underscoring the importance of plants in the bio-removal processes (phytoremediation). These results reveal that incorporating ornamental plants in TWs with TZ for wastewater in rural areas holds great promise for enhancing the visual appeal of these systems and ultimately gaining public approval. Our findings also enable us to offer recommendations for selecting suitable plants and substrates, as well as designing combinations for TWs.